2009
DOI: 10.1103/physrevb.79.155411
|View full text |Cite
|
Sign up to set email alerts
|

Stability of charged Si-doped heterofullerenes: A first-principles molecular dynamics study

Abstract: We study the structural stability of the singly and doubly charged ͑positively and negatively͒ Si-doped heterofullerene C 30 Si 30 via density-functional theory calculations combined with first-principles molecular dynamics. Geometry optimization aimed at establishing the most stable configurations at T = 0 K shows that C 30 Si 30 undergoes very limited changes in the bond lengths after addition or extraction of one or two electrons. Consideration of thermal motion reveals that the dynamical stability is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…It appears that increased doping does not stretch the Si-Si bonds significantly, confirming the trend observed in Ref. [15].…”
Section: -3supporting
confidence: 88%
“…It appears that increased doping does not stretch the Si-Si bonds significantly, confirming the trend observed in Ref. [15].…”
Section: -3supporting
confidence: 88%
“…In theory, a number of heterofullerenes containing one or more heteroatoms have been investigated, such as B,14 Si,15 Ti,16 N,17 O,18 S,19 and Xe,20 among which oxygen‐doped fullerenes have been relatively more intensively studied. The neutral C 59 O and positive species C 59 O 2+ were predicted to have cage‐opened and cage‐closed structures, respectively 19.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, the study of the structural and electronic properties of semiconductor nanoclusters has been an extremely active area of research due to their importance in nanoscience and nanotechnology [1][2][3][4]. Silicon carbide clusters are the subjects of intensive studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Recent theoretical investigations (for example, [14][15][16][17][18][19][20]) indicated that small SiC clusters prefer three-dimensional cage-like structures, and the distinct separation between the two parts of Si atoms and C atoms is energetically favourable.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide clusters are the subjects of intensive studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Recent theoretical investigations (for example, [14][15][16][17][18][19][20]) indicated that small SiC clusters prefer three-dimensional cage-like structures, and the distinct separation between the two parts of Si atoms and C atoms is energetically favourable. However, because of the lack of sp 2 hybridization of the valence orbitals of silicon atoms in SiC clusters, the empty SiC cage-like structures are likely unstable.…”
Section: Introductionmentioning
confidence: 99%